Aspetti pratici nel sacramento della riconciliazione riguardanti la protezione dei minori e degli adulti vulnerabili - Incitti, Giacomo (2020)
Scopo di questo articolo è esaminare la responsabilità del confessore in ambito di protezione dei minori e adulti vulnerabili. In tale prospettiva vengono considerati i casi in cui il penitente è l’abusatore, la vittima o anche una terza persona. Poiché non è permesso condizionare l’assoluzione alla previa autodenuncia all’autorità civile, quale spazio resta al confessore circa la pur necessaria autodenuncia del penitente in foro esterno? Quale il ruolo del Vescovo al quale è anche riservata la concessione della facoltà di ascoltare le confessioni? In questa ottica l’articolo offre qualche indicazione anche in ambito di formazione al ministero sacro.
Practical Aspects of the Sacrament of Reconciliation Affecting the Protection of Minors and Vulnerable Adults. The aim of this article is to examine the responsibility of the confessor in a few concrete cases that might arise in the confessional, when the penitent is a cleric abuser, or the victim, or when the penitent is a third party. If it is never permitted to impose on the penitent, as a condition for absolution, the obligation to turn himself in to civil authorities, what about self-reporting and absolution? In this context, the issue of abuses calls for the serious consideration of the meaning of reserving the concession of the faculty to hear confessions to the Bishop. It is necessary that the Bishop be responsible for the completion of the sacramental path. Some operative conclusions, also in view of the topic of formation.
Keywords: Beichtvater; Sünder; Sünderin; Absolution; Beichtgeheimnis